Dermoscopic surprises in a series of 6 cases - Subrata Malakar; Purva Mehta; Samipa Mukherjee; Surit Malakar (Our Dermatology Online, 2018)
Dermoscopy is a non invasive technique which can be a fantastic diagnostic tool in dermatology. Here we present a series of six cases where a dermoscopy threw light on the clinical diagnosis of lesions. Case 1A, 1B and 1C presented with singular papular lesions which led us to differential diagnosis of viral infections, seborrheic keratoses etc. However, on dermoscopy all three cases exhibited a white mass with a keratin plug and peripheral hair pin blood vessels. Our second case presented with a nodule on the nose leading us to a diagnosis of an intradermal nevus. Dermoscopy of this lesion demonstrated the presence of arborizing vessels thus indicating something far more sinister than a nevus. Case 3 was a female who presented with a small asymptomatic lobulated mass leading us to consider either seborrheic keratosis or dermatofibroma as diagnosis. But the dermoscopy correctly showed the presence of lacunae and a whitish veil which established the final diagnosis. Our final case presented with a greyish nodule suggestive of dermatofibroma. On dermoscopy, the presence of cerebriform structures and comedo like openings on the background of a white scar like patch highlighted the superimposition of another lesion on the existing dermatofibroma. Our cases prove the utility of dermoscopy as a diagnostic tool in clinical dermatology.